SUBSTANTIATION AND EXPERIENCE OF THE VARICELLA VACCINE USAGE IN VOLGOGRAD - L. V. Kramar’; A. A. Аrova; E. A. Seikina; А. М. Аlyushin (Вопросы современной педиатрии, 2012)
The authors analyse the varicella morbidity in Volgograd. The main markers of the severity of the disease course in children are estimated retrospectively. Also the economical costs of the indoor patients treatment and annual economical losses are assessed. The article contains the results of the realization of the regional programme «Vaccination», during which 14 000 children were vaccinated with «Okavax». This programme showed both high efficiency and safety.